Impact of the Adoption of Advanced Information and Communication Technologies on Firm Performance in the Canadian Manufacturing Sector - Baldwin, John R.. (OECD Publishing, 2002)
This paper investigates the evolution of the industrial structure in the Canadian manufacturing sector and its relationship to technological change by examining the take-up of advanced technologies and how it is related to the stochastic growth process in the plant population. Its framework is grounded in the view that growth is a stochastic process that involves learning. Experimentation with new technologies rewards some firms with superior growth and profitability. Examining how growth is associated with the choice of different technology strategies indicates which of these is being rewarded. The evolution of this process is studied by examining the relationship between the uptake of advanced technologies and the performance of plants in the manufacturing sector. This is done by using crosssectional data on advanced technology use and by combining it with longitudinal panel data on plant performance. In particular, the paper examines the relationship between the use of information ...
Keywords: Science and Technology; Canada